Common origin of all three coronary arteries from the right sinus of Valsalva – first case study accompanied by mitral valve prolapse and vein anomaly, second case study followed by successful percutaneous coronary intervention of right coronary artery stenosis - Przywara-Chowaniec, Brygida; Puzio, Agata; Czarnecki, Łukasz; Kawecki, Damian; Głowacki, Jan; Nowalany-Kozielska, Ewa; Czarnecka, Aleksandra (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Congenital anomalies of the coronary arteries can be divided into two broad categories: those that alter myocardial perfusion and those that do not. In coronary anomalies not altering myocardial perfusion, the coronary arteries originate from the aorta, but their origins are in unusual positions. Although myocardial perfusion is normal, the angiographer may have trouble locating them. Patients with an anomalous left main coronary artery arising from the right sinus of Valsalva are presented. The diagnosis was made by coronary angiography, transesophageal echocardiography and multislice computed tomography (MSCT). We present two cases: the first patient with coronary abnormalities had accompanying venous anomaly of lower extremities and mitral valve prolapse as well. The second patient had a history of anterior wall myocardial infarction and angioplasty with stent implantation. The extraordinary passage of the left coronary artery between the pulmonary trunk and sternum, undetectable in coronarography, was discovered due to MSCT.